Implementation of an HTML-Based Frontend in a Management Member Profiling System for the Association of Indonesian Academics and Scientists (ASASI) West Nusa Tenggara: IMPLEMENTASI FRONTEND BERBASIS HTML PADA SISTEM PROFILING PENGURUS PERKUMPULAN AKADEMISI DAN SAINTIS INDONESIA (ASASI) DAERAH NUSA TENGGARA BARAT (NTB) - Dwi Ratnasari; Aditya Rahmatdiyansyah; Soni Ariawan; Dian Syafitri Chani Saputri; Teti Zubaidah (Jurnal Begawe Teknologi Informasi (JBegaTI), 2026)
The development of information technology has encouraged organizations to improve information management. However, the Association of Indonesian Academics and Scientists (ASASI) West Nusa Tenggara does not yet have an integrated web-based system for managing and presenting management member profiles. As a result, profile information is scattered, lacks structure, and is difficult for both internal members and the public to access. Additionally, management members have limited ability to independently manage and update their profile data. This study aims to design and implement an HTML-based frontend for a management member profiling system that enables both visualization and self-management of profile data. The system is developed using HTML, CSS, and PHP native without frontend frameworks or RESTful APIs to ensure simplicity, ease of maintenance, and suitability to organizational needs. The effectiveness of this approach is evaluated using usability, accessibility, and maintainability indicators, including ease of navigation, clarity of information presentation, and minimal dependency on external frameworks. The results show that the system successfully provides structured and user-friendly profile information while enabling efficient data management by users. The system improves transparency, enhances information dissemination, and supports more effective organizational management in the digital era.